Інтегрований підхід до оцінки цифрової трансформації IT-бізнес-процесів у контексті ЦСР - Лисенко, Сергій Миколайович (Міжнародний університет бізнесу і права, 2025)
У статті запропоновано інтегрований підхід до вибору індикаторів для оцінки впливу цифрової трансформації на управління бізнес-процесами ІТ-компаній з урахуванням цілей сталого розвитку. Дослідження об’єднує метод експертних оцінок, контент-аналіз міжнародних стандартів (ISO 9001:2015, SDG Compass, DMM), а також індексний підхід до нормалізації показників. Автором сформована система індикаторів за напрямами ефективності, якості, цифрової зрілості та сталості з можливістю подальшої агрегації в інтегральний індекс. Запропоновано чітку послідовність оцінювання, що включає ідентифікацію процесів, формалізацію індикаторів, збір емпіричних даних, вагове ранжування, побудову профілю цифрової трансформації компанії та визначення управлінських рекомендацій. Такий підхід дозволяє ІТ-компаніям підвищити прозорість і точність оцінки змін, оптимізувати управлінські рішення відповідно до стандартів якості та орієнтації на ЦСР. Практичне застосування моделі може допомогти у визначенні цифрових пріоритетів, дотриманні ESG-стратегій та побудові ефективної дорожньої карти трансформації.

This article proposes an integrated approach for selecting indicators to assess the impact of digital transformation on business process management within IT companies, emphasizing alignment with Sustainable Development Goals (SDGs). The study combines methods including expert evaluations, content analysis of international standards (ISO 9001:2015, SDG Compass, Digital Maturity Model), and an index-based normalization approach. The authors constructed a comprehensive system of indicators grouped into four key dimensions: operational efficiency, management quality, digital maturity, and sustainability. Each dimension encompasses specific indicators relevant to both international benchmarks and national priorities for digital development. The proposed methodology outlines a structured sequence of assessment that includes identification of core business processes, formalization and normalization of relevant indicators using the min–max method, empirical data collection, expert-based weighting, construction of a digital transformation profile, and development of actionable management recommendations. This integrated assessment approach enhances transparency and accuracy, facilitating more informed managerial decisions that adhere to international quality standards and sustainability objectives. Practically applied, the model aids IT companies in pinpointing digital transformation priorities, strengthening their Environmental, Social, and Governance (ESG) strategies, and crafting effective transformation roadmaps. A pilot evaluation conducted with Ukrainian IT firms highlights the method’s adaptability and effectiveness, identifying digital maturity as the strongest performing area, while revealing significant opportunities for improvement in sustainability integration. The proposed approach overcomes limitations of existing frameworks by providing a balanced and comprehensive evaluation system that captures technological, managerial, and ESG aspects, thus presenting a robust tool for strategic management in the digital economy.
Integrated approach to assessing it business process digital transformation in the context of SDGs
Keywords: цифрова трансформація; управління бізнес-процесами; стандарти; сталий розвиток; ІТ-компанії; digital transformation; business processes management; standards; sustainability; IT-companies